2023
DOI: 10.1021/acs.macromol.3c00852
|View full text |Cite
|
Sign up to set email alerts
|

Polycondensation-Involved Melanin-like Polymers for Enhanced Solar Energy Utilization

Abstract: Polydopamine (PDA) and poly­(5,6-dihydroxyindole) (PDHI), both typical representatives of melanin-like polymers, are emerging as promising kinds of photothermal functional materials with a similar polymeric structure. However, the chaos of the microstructure formed by free radical polymerization of monomers still hinders the efficient regulation of their photothermal performances. Herein, we introduced condensation polymerization between aldehydes and the 5,6-dihydroxyindole (DHI) monomer during the free radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…To assess the solar evaporation ability quantitatively, the mass change of seawater was recorded. The evaporation rate of NPDA-3@PES was calculated to be 1.97 kg m –1 h –1 in Figure h, and the value was higher than that of PDA-0@PES of 1.78 kg m –2 h –1 and many other kinds of melanin-like polymer-based evaporation devices reported in previous literatures. ,, In order to test the seawater desalination performance, the concentrations of four main metal ions, including Na + , Mg 2+ , K + , and Ca 2+ , were evaluated before and after desalination by the inductively coupled plasma spectroscopy (ICP-OES), respectively (Figure i). The metal ion concentrations sharply decreased approaching to the concentration of deionized water.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…To assess the solar evaporation ability quantitatively, the mass change of seawater was recorded. The evaporation rate of NPDA-3@PES was calculated to be 1.97 kg m –1 h –1 in Figure h, and the value was higher than that of PDA-0@PES of 1.78 kg m –2 h –1 and many other kinds of melanin-like polymer-based evaporation devices reported in previous literatures. ,, In order to test the seawater desalination performance, the concentrations of four main metal ions, including Na + , Mg 2+ , K + , and Ca 2+ , were evaluated before and after desalination by the inductively coupled plasma spectroscopy (ICP-OES), respectively (Figure i). The metal ion concentrations sharply decreased approaching to the concentration of deionized water.…”
Section: Resultsmentioning
confidence: 97%
“…Nevertheless, the disordered and undefined structure of PDA hinders the effective adjustment of their energy bandgap and light harvesting performance, and the modular and efficient chemistries are highly desirable. In our previous work, regulating the energy structure and light absorption of melanin-like polymers has been realized by increasing electron donor–acceptor (D–A) microstructures within macromolecular systems. However, most typical electron D–A constructing strategies usually required sophisticated organic synthesis by involving strong oxidants and bases, probably resulting in the formation of structural defects. For those cases, the lack of robust and suitable chemical tools for the structural regulation of melanin-like polymers could hinder the establishment of the structure–function relationship in complex and disordered bioinspired macromolecules.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the all melanin composites, melanin could also be integrated with other organic building blocks to enable enhanced performance by physical blending and predoping, such as near-infrared (NIR) light absorption, antioxidation, hydration-dependent conductivity, biocompatibility, and render tremendous application. , For instance, tobramycin (TOB) is a broad-spectrum antibiotic that contains an amino group and can be copolymerized with dopamine monomers through Michael addition reaction . Antibiotics endow nanoparticles with antibacterial properties, and the excellent light adsorbing properties of PDA make it a possible photothermal composite material for solar distillation. …”
Section: Melanin-inspired Composite Materialsmentioning
confidence: 99%
“…It has been extensively shown that constructing the donor–acceptor (D–A) structures is a typical strategy for modulating the light absorption capacity in polymers. 103 The PDA system usually includes non-cyclized DA, DHI, indole-5,6-quinone (IQ), and oligomers of these units. Among them, IQ provides conjugate structures in PDA systems to achieve a wide range of light absorptions.…”
Section: Strategies For Tuning Hair Colorsmentioning
confidence: 99%
“…The chemical connection between DHI and electron-rich IQ has also been regarded as electron donor–acceptor pairs (D–A pairs), which could regulate the energy gap and light absorption properties of the PDA system. 63,103–105 Therefore, the introduction of electron acceptors could further contribute to the construction of D–A pairs with DHI, IQ, and their oligomers in the PDA system, which would induce molecular rehybridization and thus manipulate the energy structure and optical absorption (Fig. 9).…”
Section: Strategies For Tuning Hair Colorsmentioning
confidence: 99%